The Concept Of Ulul Albab In The Quran And Its Implementation In Student Character Education - Habibah Mas Ruroh; Abdul Halim (Journal of Social Science and Economics, 2023)
This article is entitled "The Concept of Ulul Albab in the Al-Qur'an and Its Implementation in Character Education for Students of MTs Al-Azhar Menganti Gresik". The research method in this thesis uses a qualitative case study approach and data collection techniques through observation, interviews, and documentation. The focus of this research is: 1) How is the concept of ulul albab in the Qur'an?, 2) How is the implementation of the concept of ulul albab in character education of students at MTs Al-Azhar Menganti Gresik? While the objectives of this thesis research are: 1) To find out how the Qur'an describes the concept of ulul albab, 2) To find out how the implementation of the concept of ulul albab in character education of students at MTs Al-Azhar Menganti Gresik. The results of this thesis research are: 1) The concept of ulul albab in the Qur'an is described as a person who tries to explore the Oneness of his God by always thinking about His creation. 2) The concept of ulul albab at MTs Al-Azhar is carried out with istikamah activities and with continuous improvement efforts. Because it refers to character education from an Islamic perspective, where there is no separate discipline from Islamic ethics. The comparison between reason and revelation in determining the character of a student is very important. Until the main values that must be possessed by a student of knowledge other than knowledge itself, namely morals, etiquette, and example.